2016
DOI: 10.1016/j.vaccine.2016.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Novel HLA-A2-restricted human metapneumovirus epitopes reduce viral titers in mice and are recognized by human T cells

Abstract: Human metapneumovirus (HMPV) is a major cause of morbidity and mortality from acute lower respiratory tract illness, with most individuals seropositive by age five. Despite the presence of neutralizing antibodies, secondary infections are common and can be severe in young, elderly, and immunocompromised persons. Preclinical vaccine studies for HMPV have suggested a need for a balanced antibody and T cell immune response to enhance protection and avoid lung immunopathology. We infected transgenic mice expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In murine studies, Kolli et al intranasally infected BALB/c mice with a laboratory strain of hMPV (CAN97-83) or exposed animals to UV-inactivated hMPV and demonstrated that the depletion of either CD4 + or CD8 + T cells compromised the animals' ability to control/clear the viral challenge [37]. Similarly, Hastings et al vaccinated HLA-A2 transgenic C57BL/6 mice with either an hMPV M-derived CD8 + T-cell epitope or irrelevant control, challenged them with a live hMPV strain (TN/94-49), and demonstrated that the viral load in the lungs of vaccinated animals was significantly lower than that for control mice [38]. Finally, Herd et al demonstrated that T cells with an effector profile, characterized by production of both prototypic Th1 cytokines (IFN-γ, GM-CSF, and interleukin 12) and proinflammatory chemokines (macrophage inflammatory protein 1α and IFN-γ-inducible protein 10), were able to accumulate at the lung following hMPV infection [39].…”
Section: Discussionmentioning
confidence: 99%
“…In murine studies, Kolli et al intranasally infected BALB/c mice with a laboratory strain of hMPV (CAN97-83) or exposed animals to UV-inactivated hMPV and demonstrated that the depletion of either CD4 + or CD8 + T cells compromised the animals' ability to control/clear the viral challenge [37]. Similarly, Hastings et al vaccinated HLA-A2 transgenic C57BL/6 mice with either an hMPV M-derived CD8 + T-cell epitope or irrelevant control, challenged them with a live hMPV strain (TN/94-49), and demonstrated that the viral load in the lungs of vaccinated animals was significantly lower than that for control mice [38]. Finally, Herd et al demonstrated that T cells with an effector profile, characterized by production of both prototypic Th1 cytokines (IFN-γ, GM-CSF, and interleukin 12) and proinflammatory chemokines (macrophage inflammatory protein 1α and IFN-γ-inducible protein 10), were able to accumulate at the lung following hMPV infection [39].…”
Section: Discussionmentioning
confidence: 99%
“…CD8 + T cells are critical during respiratory virus infections, as they are the primary cell type that will aid in the clearance of infected cells [ 52 ]. Lack of CD8 + T cells during hMPV infections resulted in more severe diseases and increased viral loads, while adoptive transfer of this cell type aids in the clearance of this virus [ 40 , 52 , 131 ]. CD8 + T cells (also termed cytotoxic lymphocytes (CTL)) usually secrete IFN-γ as part of the antiviral response [ 132 ].…”
Section: Components and Cells Of The Adaptive Immune System Responmentioning
confidence: 99%
“…Hastings et al studied HLA-A*02:01-restricted human epitopes in HLA-A2 transgenic mice using adjuvanted peptide immunization; two peptides were also studied in human PBMCs. The M39 peptide was demonstrated to have protective potential in a mouse challenge model [ 95 ]. Erickson et al mapped two CD8 epitopes using HLA-B7 transgenic mice, which can only recognize human HLA-B*0702 CD8 T-cell epitopes [ 46 ].…”
Section: Prospects Of and Barriers To The Development Of Epitope-bmentioning
confidence: 99%